Perubahan Morfofisiologis Tanaman Terung pada Kondisi Muka Air Tanah Dangkal dan Tergenang di Fase Generatif - Mei Meihana; Erna Siaga; Benyamin Lakitan (Institut Pertanian Bogor, 2023)
Under suboptimal conditions, plants generally respond differently to survive. Plant responses include changes in morphology, anatomy, and physiology. This study aimed to investigate the response of eggplant to lack of oxygen due to shallow water table and waterlogging in the generative stage and explored their adaptability to be cultivated in riparian wetlands. This research was conducted from October 2017 to January 2018 in an experimental pond in the village of Demang Lebar Daun Palembang and at the Postgraduate Integrated Laboratory, Faculty of Agriculture, Sriwijaya University, Palembang. This study used a randomized block design with a shallow water table and waterlogging treatments: control (field capacity), water tables of 13 cm, 8 cm, and 3 cm below the soil surface (bss), and waterlogging 2 cm above the soil surface. The results showed that the water table 3 cm bss and waterlogging decreased the relative rate of leaf expansion, specific leaf fresh weight, and specific leaf water content. On the sixth day of the waterlogging treatment, the chlorophyll content decreased by 31.29%. On the other hand, the proline content in the leaves reached the highest level of concentration. After the sixth day, the chlorophyll content increased while the proline content decreased, and the eggplant recovered. Water table 3 cm bss and waterlogging caused the formation of aerenchyma tissue in the roots, which started one day after the treatment. Eggplant is an adaptive crop with a fairly high tolerance for shallow water tables and waterlogging. Keywords: adaptation, aerenchyma, proline, riparian wetland, tolerance